Money Growth and Velocity with Structural Breaks: Evidence from the Philippines - Baunto, Assad L.; Bordes, Christian; Maveyraud, Samuel; Rous, Philippe (Philippine Management Review, 2011)
This paper aims to test the Friedmanite proposal on the link between the velocity of money demand and money growth. We base our work on the Philippines as its monetary policy has been subject to sharp swings since the 1980s. We use a method that takes into account possible structural breaks in the velocity of money demand and a GARCH model to evaluate the variability of money growth. We apply Granger causality tests to confirm the Friedmanite hypothesis.
Keywords: Friedman hypothesis; GARCH; structural breaks